PREDICTIVE MAINTENANCE OF THE AUTOMATED SEWING MACHINES IN TEXTILE INDUSTRY - ŞUTEU Marius Darius; BABAN Calin Florin; BABAN Marius; DRAGOMIR George; OTH (Kiss) Edit (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2019)
One of the most used approaches to schedule maintenance is condition-based maintenance. The automated sewing machines are state-of-the-art complex machines that operate at high speeds, where vibrations and noises are generated by their moving parts. The levels of vibrations and noises increase at the high-speed working regime and when some components are worn out. Within this context, the aim of this paper was the development of a software product based on fuzzy logic to schedule the replacement of the needles of the automated sewing machines based on their condition monitoring. The research was carried out on an automated sewing machine that operated at the recommended working speed of 3500 stitches/minute. The sewing material was polyester and NM 80 sewing needles were used. Vibration measurement was performed using the Top Lab-GBDT-L device, while the Center 322 sonometer was employed to measure the level of noise. The integrated software environment R was employed to develop the software product. This software allows the establishment of the time when the replacement of these needles should be done taking into account their noise level and vibrations amplitude. An example demonstrates the effectiveness of the software product for the replacement of the needles of automated sewing machines.